1982
DOI: 10.1007/bf01257989
|View full text |Cite
|
Sign up to set email alerts
|

Perisomatic changes in the maturing hypoglossal nucleus after axon injury

Abstract: The perisomatic retrograde reactions to peripheral nerve injury during postnatal maturation were investigated by quantitative light and electron microscopy. The hypoglossal nerve was crushed, ligated or transected in 10 and 21 day postnatal (dpn) rats. Only crush injury was made in 7 dpn rats. Survival periods ranged from 3 to 40 days postoperative (dpo). Normal and sham operated animals of corresponding ages served as controls. A remarkable, transient response of neuronal somata in the young (7-10 dpn) rats, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…54 Similarly it has also been shown that injured hypoglossal motor neurons envelop synapses innervating the cell soma. 55 It is not clear from these studies what is the mechanism of recognition of the supernumerary synapses or the fate of the enveloped synapses. A recent study has proposed that during development supernumerary retinal ganglion cell synapses in the dorsal lateral geniculate nucleus are tagged by C1q and C3 synthesized by the retinal ganglion cells and subsequently removed by the microglia present in the vicinity.…”
Section: Synaptic Degeneration In Prion Diseasementioning
confidence: 99%
“…54 Similarly it has also been shown that injured hypoglossal motor neurons envelop synapses innervating the cell soma. 55 It is not clear from these studies what is the mechanism of recognition of the supernumerary synapses or the fate of the enveloped synapses. A recent study has proposed that during development supernumerary retinal ganglion cell synapses in the dorsal lateral geniculate nucleus are tagged by C1q and C3 synthesized by the retinal ganglion cells and subsequently removed by the microglia present in the vicinity.…”
Section: Synaptic Degeneration In Prion Diseasementioning
confidence: 99%
“…A detailed account of the methods used in this study has been published previously (Borke, 1982). Two hundred and thirty-two male rats of the Osborn-Mendel strain were used for this work.…”
Section: Methodsmentioning
confidence: 99%
“…Marked amplification of the existing structural arrangement in neuronal perikarya suggests acceleration of the patterns of protein synthesis operating in the young neuron at the time of injury. However, the continued production of organized RER as well as the elaborations of somal excrescences after nerve injury (Borke, 1982) provide evidence that the synthetic processes were not directed exclusively toward axonal replacement and point out that a certain level of somal maturation may be necessary for the selective production and/or utilization of materials for axonal regrowth.…”
Section: Timetable Of Nuclear and Organized Rer Involvement In The Inmentioning
confidence: 95%
See 2 more Smart Citations